FINANCIAL DISTRESS PADA SEKTOR BANK CAMPURAN DI INDONESIA DENGAN RASIO CAMEL SEBAGAI ALAT UKUR. PERIODE STUDI 2014 – 2019. - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to analyze the effect of the CAMEL ratio as measured using the ratio of CAR, NPL, ROA, ROE, LDR and BOPO to financial distress in the mixed bank sector in Indonesia for the period 2014-2019. Data were analyzed using multiple regression and hypothesis testing F test for simultaneous effect and T test for partial effect. The results of this study indicate that the ratio of CAR, NPL, ROA, ROE and LDR partially has no significant effect on Financial Distress, while BOPO has a significant effect on Financial Distress. However, simultaneously the six ratios have an effect on the Financial Distress of Indonesian banks